Bour s theorem on gauss map in 3 euclidean space - Güler, Erhan; Yaylı, Yusuf; Hacısalihoğlu, Hasan Hilmi (Hacettepe Üniversitesi, 2010)
In this paper some relations are established between the Laplace-Beltrami operator and the curvatures of helicoidal surfaces in 3-Euclidean space. In addition, Bour’s theorem on the Gauss map, andsome special examples are given.
Keywords: Rotational surface; Helicoidal surface; Gauss map; Laplace-Beltrami operator; Minimal harmonic surface